Ageing Narratives and Social Change in Kathmandu: An Ethnographic Study of Personhood and Well-being - Pokharel, Saroj; Adhikari, Bhawani Shanker; Dahal, Shree Ram; Dangol, Dinesh; Maharjan, Gyan Bhakta (Exploration अन्वेषण, 2026)
In the Tarkeshwor Municipality of Kathmandu, this qualitative ethnographic study explores the lived experiences and narratives of those aged 60 and attempts to place the narratives within the context of the rapid demographic changes within the municipality, which include urbanisation and youth outmigration. Within the framework of Symbolic Interactionism and Theories of Personhood within Anthropology, this research utilises qualitative methodology in the form of participant-observed semi-structured interviews of 40 respondents to study the ways mega-level societal changes impact the intergenerational relations and social positioning of individuals and their overall wellness. One primary finding suggests there is a significant phenomenon of cultural tension relative to the older adults at the intersection of socio-economically modern realities in the context of the social value of older adults, and cultural systems that place older adults within a socially revered role. The primary forms of financial capital, such as pensions and real estate, are the socially positioned structures of value and independent relational social identity, and chronic health problems serve as social and relational loss catalysts. The study suggests that the ageing of urban Nepal is an identity-contested process relative to the social systems of support for older adults, which does not rely on frameworks of social security systems and biomedicine.